THE IMPACT OF FINANCIAL INCLUSIVE FOR ENSURING APPROPRIATE THE CUSTOMER SATISFACTION INDEX (CSI) AND IMPORTANCE PERFORMANCE ANALYZE (IPA) OF CSR PROGRAM IN SME’S BATIK LASEM - Azis Fathoni (Jurnal Ekonomi dan Bisnis Kontemporer, 2018)
The shift of the economic structure from agriculture sector to processing industry or trade and services sector raises some new potential in some areas. The development of the potential area can be measured by the identification model of strategic sector potential and model of creative position strengthening of Small and Medium Enterprises which is useful to raise competitiveness.The measured potential is not yet fully covered in a financing model from the micro finance level facilitated by investors to help small and medium enterprises grow up.This study conducted two tests namely feasibility test and Importance Performance Index Test. For the feasibility of this research is to use analysis of development of Small and Medium Business Area of Kampung Batik in Lasem Rembang that is using Location Quotient, Shift Share and EFAS analysis.The other measurements are the analysis of Community Satisfaction Index (CSI) and Importance Performance Analysis (IPA) to optimize the development model of Fair Finance Guide International (FFGI) of the banking in order to know the benefits and costs incurred from banking activities in functioning as an inclusive financial institution that develops service partnerships that suit the needs of the community.The population of this research are 30 groups of business of Batik Lasem. The results of this study indicate the value of LQ1 analysis, as well as in the development of SWOT matrix is in the quadrant 1 at Coordinate (3;3.54) with progressive recommendation. For the results of processing indicators in accordance with the methodology FFGI obtained Index Value Importance Performance has not shown the overall optimal of the level of conformance between the performance of financial programs with the expectations of businessman.Key Words: Importance Performance, Location Quotient, Inclusive Financial, FFGI